2023
DOI: 10.1039/d3gc02909c
|View full text |Cite
|
Sign up to set email alerts
|

Local reactivity descriptors to decipher the electrochemical hydrogenation of unsaturated carboxylic acids

Marco Nazareno Dell'Anna,
Geet Gupta,
Prathamesh T. Prabhu
et al.

Abstract: The decarbonization of chemical manufacturing is a multifaceted challenge that requires technologies able to selectively convert CO2-sequestering feedstocks using renewable energy. The electrochemical conversion of biomass-derived platform chemicals is well-positioned...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These conclusions are consistent with our recent experimental studies showing that these steps can occur as outer-sphere PCET processes, with similar rates and selectivity for Pb, Bi, Pd, and Pt foils suggesting that the step is not directly surface-mediated. 33,35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These conclusions are consistent with our recent experimental studies showing that these steps can occur as outer-sphere PCET processes, with similar rates and selectivity for Pb, Bi, Pd, and Pt foils suggesting that the step is not directly surface-mediated. 33,35…”
Section: Resultsmentioning
confidence: 99%
“…1, previous studies have shown that cc MA electrochemical hydrogenation (ECH) to AA was surprisingly challenging, and instead selectively produced the monounsaturated diacid trans -3-hexenedioic acid ( t 3HDA). 33–35 Such monounsaturated acids have been recently shown to find applications in synthesizing performance-advantaged nylons. 36…”
Section: Introductionmentioning
confidence: 99%